Challenges faced by rural accounting teachers in implementing web-based collaborative learning - Thabiso Jonah Motsoeneng; Henry James Nichols; Sekitla Daniel Makhasane (Perspectives in Education, 2021)
The twenty-first century has witnessed a call for teachers to integrate information and communication technology (ICT) into teaching and learning. However, creating a classroom environment that engages in active learning has proved to be a hurdle to South African teachers, as more traditional teaching methods continue to be utilised in teaching. These challenges have derailed the current efforts by the Department of Basic Education to introduce ICT in the teaching and learning process in an effort to create a learner-centred environment. This paper seeks to open epistemic access by determining the challenges faced by rural accounting teachers in implementing web-based collaborative learning. The paper reports on the findings of a qualitative study that employed interviews to generate data with five Grade 10 accounting teachers in rural South Africa. The findings reveal that accounting teachers are faced with myriad challenges that serve as a stumbling block in their attempt to implement web-based collaborative learning. Contrary to the principles of Critical Accounting Research, the teaching methods and resources used position teachers in control and authority while the learners are disempowered, marginalised and oppressed. We consequently argue that accounting teachers require support and capacity building to implement web-based collaborative learning effectively.